Electronic Voting in the 2013 Kenya Elections - (:unkn) unknown (My University, 2013)
Journée d'études LAM-UPPA avec l'IFRA Nairobi, Session Legal Aspects from a Multidisciplinary Perspective http://lamuppa.univ-pau.fr/live/digitalAssets/126/126969_PROGDEF.pdf
Keywords: African Research